Forage seed system in Tanzania - a review report - Ngunga, David; Mwendia, Solomon W. (Bioversity International and the International Center for Tropical Agriculture, 2020)
As feed and feeding take most of the input to realized increased livestock productivity, access to good quality forages for livestock especially dairy and beef animals is key. Over year, and especially in sub-Saharan Africa forage breeding and improvement has been dormant, and rely on maintaining materials developed decades ago, and still with limited access by livestock producers. We set out to understand the prevailing forage seed system in Tanzania, the functioning and use of improved forages for a country with the third highest livestock population in Africa. While subtle forage seed is happening largely by public institutions, there exist room for improvement especially through engaging public private partnership, and explore use of elite forages developed elsewhere that may be beneficial.